Dashboard Visualization of Mobility COVID-19 / Noor Syarafana Nordin and Noorfaizalfarid Mohd Noor - Nordin, Noor Syarafana; Mohd Noor, Noorfaizalfarid (College of Computing, Informatics and Media, UiTM Perlis, 2023)
COVID-19 is now declared as global pandemic by World Health Organization. These coronaviruses spread among animals and even in humans such as camels, pigs, cats, and bats. COVID-19 stands for Coronavirus disease 2019, it was first identified on 17 November 2019 in Wuhan, China. The symptoms of COVID-19 are some other flu diseases such as fever, sore throat, tiredness, nasal congestion, and headache. It is hard to find out the difference between common flu and COVID-19. Now, this virus is spread out throughout the world. The Dashboard Visualization of Mobility COVID-19 is a graphical data visualization to assist and help people to concerned about COVID-19, gain knowledge about COVID-19 and to make big look at the effect of this diseases since it exists.